Hospitality law : managing legal issues in the hospitality industry / Stephen C Barth, David K Hayes - Barth, Stephen C
"Encouraging readers to think critically about legal concepts related to hospitality, Hospitality Law, Second Edition is an indispensable part of every hospitality manager's education."--Jacket.